Peran Influencer sebagai Komunikasi Persuasif untuk Pencegahan Covid-19 - Sukma Alam (Jurnal Spektrum Komunikasi, 2020)
ABSTRACT The existence of influencers is important in information disclosure in the midst of the COVID-19 pandemic. Because, influencers are people who have influence in disseminating information and experiences in a persuasive manner. This research uses a case study method with informant interviews, namely influencers who are officially collaborating with BNPB as volunteers of the COVID-19 Task Force. The results of this study show that the role of influencers has a significant impact on their followers. Content created by influencers in an effort to prevent COVID-19, uses an approach that is persuasive or solicitous in that each content is inserted with education and prevention socialization as well as content that does not contain conversion. To reach people who cannot access the internet, influencers go to the field to communicate directly to meet community leaders, public figures and regional heads. This creates trust between users and their followers, so these influencers have succeeded in having loyal followers. Keywords: Influencers, Persuasive Communication, COVID-19